Code-switching in Bilingual Classroom in Sri Lanka: Differing Perception of Teacher and Students - Abeywickrama, Rohan (English Department, Faculty of Humanities, Andalas University, 2023)
Code-switching occurs in multilingual cultures where citizens have the right and ability to speak two or more languages. This phenomenon can frequently be seen in the English Medium classrooms in the Sri Lankan state school where English and Sinhala are used interchangeably for classroom practices. This article aims to examine subject teachers’ and students’ perspectives towards the use of English and Sinhala for instruction and learning in English medium classrooms in state schools in Sri Lanka, thus identifying how code-switching impacts on students’ performance. The study used mixed method for data collection. Five English medium teachers of three schools in the Hambantota district in Sri Lanka were interviewed and forty students who are learning the subjects in English medium in five schools were distributed questionnaires. The study used random sampling method for selecting the participants and Thematic Analysis (TA) for identifying, organizing, and interpreting data. One key finding of this study is that most teachers employ code-switching in bilingual classrooms in order to make the students familiarize with the subject matter. Although the majority of students are willing to speak English, as a medium of instruction in bilingual classrooms, students need their teachers to explain the lessons in both media. Although code-switching can enhance a student’s knowledge of a specific subject it does not make the student a better speaker or a writer. The current study has implications for bilingual teachers, students, syllabus, and material designers.